2017
DOI: 10.1002/ehf2.12201
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular involvement and the extent of left ventricular enhancement with magnetic resonance predict adverse outcome in pulmonary sarcoidosis

Abstract: AimsCardiac involvement is the main determinant of poor outcomes in sarcoidosis. Right ventricular (RV) dysfunction and left ventricular (LV) late gadolinium enhancement (LGE) have been reported to be predictive of adverse outcome in non‐ischaemic cardiomyopathies. The aim of our study was to determine whether delayed RV LGE with cardiovascular magnetic resonance would be predictive of adverse events in addition to LV LGE during the long‐term follow‐up of pulmonary sarcoidosis patients.Methods and resultsEight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Multiple studies have demonstrated that late gadolinium enhancement is associated with increased all-cause mortality and increased ventricular arrhythmias when compared with those without LGE [7][8][9]. Quantity of LGE also appears to be related to the risk of future SCD, for example, in one study, absence of > 8% LGE of LV myocardium had a 95% negative predictive value [39]. The presence of FDG uptake and perfusion defects on PET is associated with higher risk of death or VT [12].…”
Section: Risk Stratification For Sudden Cardiac Deathmentioning
confidence: 99%
“…Multiple studies have demonstrated that late gadolinium enhancement is associated with increased all-cause mortality and increased ventricular arrhythmias when compared with those without LGE [7][8][9]. Quantity of LGE also appears to be related to the risk of future SCD, for example, in one study, absence of > 8% LGE of LV myocardium had a 95% negative predictive value [39]. The presence of FDG uptake and perfusion defects on PET is associated with higher risk of death or VT [12].…”
Section: Risk Stratification For Sudden Cardiac Deathmentioning
confidence: 99%
“…7). 84 Location may also be important; in 51 patients with CS and LVEF >35%, the presence of RV-delayed enhancement was associated with an increased risk of VT/VF or death. 85 Cardiac PET is also emerging as a modality that may help with risk stratification.…”
Section: Iiamentioning
confidence: 99%
“…PET scan has also been evaluated in predicting supraventricular arrhythmias, and it was noted that patients with left atrial enlargement were associated with increased likelihood of supraventricular arrhythmias [11]. Smedema et al reported that biventricular late gadolinium enhancement was the strongest predictor of adverse outcome, and an asymptomatic myocardial scar of less than 8% in the left ventricular mass was associated with a favorable outcome in patients with pulmonary sarcoidosis [12].…”
Section: Positron Emission Tomography Scanmentioning
confidence: 99%